2008
DOI: 10.4141/cjss07014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different soil management practices on soil free-living nematode community structure, Eastern China

Abstract: . 2008. Effects of different soil management practices on soil free-living nematode community structure, Eastern China. Can. J. Soil Sci. 88: 115Á127. An investigation was conducted in a Shouguang agroecosystem, Shandong Province, Eastern China, in order to determine the long-term (10Á15 yr) disturbances of three different agricultural management practices. In this study, the main focus was on free-living soil nematodes, as a tool which will help differentiate between treatments according to their sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 40 publications
4
8
0
1
Order By: Relevance
“…Bacterivores were the most abundant trophic group in all three systems, which is in accordance with previous findings (Liu et al 2006;Chen et al 2008;Dong et al 2008) that bacterivores were dominant in greenhouse conditions. However, the proportion of bacterivores (more than 80%) was higher relative to the abovementioned studies.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Bacterivores were the most abundant trophic group in all three systems, which is in accordance with previous findings (Liu et al 2006;Chen et al 2008;Dong et al 2008) that bacterivores were dominant in greenhouse conditions. However, the proportion of bacterivores (more than 80%) was higher relative to the abovementioned studies.…”
Section: Discussionsupporting
confidence: 92%
“…Compared with other studies (Liu et al 2006;Chen et al 2008;Dong et al 2008;Li et al 2010) of greenhouse conditions, our findings revealed a higher proportion of omnivore-carnivores, and this proportion was close to that of another report (7.8%) in an open farmland environment (Hu & Qi 2010) near our study site. Forge et al (2005) noted that manure applied may enhance the availability of food resources for the nematodes of high-order trophic groups.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Because of the Tyelenchidae family's ambiguous position in the soil food web [62], it was interesting to find that, in both seasons, nematodes from the Tylenchidae family showed a similar trend in correlations with CO 2 , N min and yield as the FF nematodes. In nematode trophic analysis it is unclear whether to place Tylenchidae among the plant parasitic nematodes or the fungal-feeders [63][64][65][66][67]. These findings suggest that, in our case, Tylenchidae are more closely associated with fungal-feeders.…”
Section: Using Nematodes In the Measurement Of Soil Health In Agriculmentioning
confidence: 79%